Pengaruh Kualitas Jasa Pelayanan terhadap Kepuasan Pengguna Jasa Layanan di Universitas Brawijaya (Studi di Fakultas Ilmu Administrasi, Fakultas Teknik dan Fakultas Ekonomi dan Bisnis) - Apriandani, Rizki (Jurnal Ilmiah Administrasi Publik, 2016)
Malang is well-known as education city because there are many university in Malang. With many universities, high school graduate or equivalent as prospective students can more freely to choose and determine their future place of study in Malang. Based on this, University of Brawijaya (UB) has grade A accreditation with good international reputation based on webometric and QS star. The purposes of the study was to know the effect of service quality on satisfaction in UB based on four dimension: (1) reliability; (2) empathy; (3) tangible; and (4) responsiveness. Method used was explanatory research using quantitative data and analysis technique in order to answer the relationship between variable via hypothetical test. Data were collected from 98 respondent via interview using questionnaire. The collected data then analyzed using multiple regression analysis with t-test and f-test. The results showed that service quality, which consists of reliability, empathy, tangible, and responsiveness, had significant effect (P<0.05) with satisfaction simultaneously and partially. The most dominant variable was responsiveness.